Comparative genome analysis of morphologically distinct populations of Rhipicephalus sanguineus (Latreille, 1806) - Carvalho, Mário André Barbosa de (2024)
Tese de mestrado, Biologia Humana e Ambiente, 2024, Universidade de Lisboa, Faculdade de Ciências